The intelligent investor : the definitive book on value investing - Graham, Benjamin, 1894-1976; Zweig, Jason (Harper Business, an Imprint of HarperCollins Publishers, 2024)
"The classic work on investing, filled with sound and safe principles, now revised with an introduction and appendix by Warren Buffett-one of the author's students-and newly updated commentaries on each chapter from Wall Street Journal writer Jason Zweig"--